2014
DOI: 10.3390/molecules19022469
|View full text |Cite
|
Sign up to set email alerts
|

Novel Lycorine Derivatives as Anticancer Agents: Synthesis and In Vitro Biological Evaluation

Abstract: Lycorine, which is the most abundant alkaloid isolated from the Amaryllidaceae family of plants, reportedly exhibits promising anticancer activities. Herein, a series of novel lycorine derivatives were synthesized and evaluated for their in vitro inhibitory activities against seven different cancer cell lines, including A549, HCT116, SK-OV-3, NCI-H460, K562, MCF-7 and HL-60. The results indicated that compounds bearing diverse amine substituents at the C-2 position demonstrated good anticancer activities. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 19 publications
1
22
0
Order By: Relevance
“…The lycorine ( 2 ) we used for subsequent derivation was obtained as a hydrochloride salt ( 1 ), which was commercially available, more stable and much less expensive. Compounds 2 – 5a , 8 , 9 , 10 , 12 , 14 and 15 (Scheme S1) were prepared according to the procedures reported previously. Compounds 5 – 7 (Scheme ), 11 (Scheme ), 13 (Scheme ), 16 and 17 (Scheme ) were prepared using our methods.…”
Section: Resultsmentioning
confidence: 99%
“…The lycorine ( 2 ) we used for subsequent derivation was obtained as a hydrochloride salt ( 1 ), which was commercially available, more stable and much less expensive. Compounds 2 – 5a , 8 , 9 , 10 , 12 , 14 and 15 (Scheme S1) were prepared according to the procedures reported previously. Compounds 5 – 7 (Scheme ), 11 (Scheme ), 13 (Scheme ), 16 and 17 (Scheme ) were prepared using our methods.…”
Section: Resultsmentioning
confidence: 99%
“…The initial aim of the resent study was to verify the inhibitory effect of lycorine derivatives on enterovirus. Rapid phenotype screening was performed using a total of 26 previously synthesized lycorine derivatives (33,36) to assay the inhibitory activity of these molecules against EV71-GFP ( Table 1). Most of the tested compounds did not exhibit an anti-EV71 effect at a concentration of 40 M, with two significant exceptions: treatment with compounds 18 (1acetyllycorine) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Lycorine derivatives and reagents. Lycorine derivatives were synthesized by our group (Table 1) (33,36). Stock solutions at a concentration of 10 mM were prepared in distilled water with dimethyl sulfoxide (DMSO) and diluted in DMEM with 10% FBS to different concentrations before use.…”
Section: Methodsmentioning
confidence: 99%
“…However, chemotherapy and radiotherapy usually lead to serious adverse effects, such as impairment of the hematopoietic and immune systems [26]. With the rapid development of traditional Chinese medicine with modern medical technologies in the last several decades, numerous studies have found that E. fischeriana Steud [27,28], norcantharidin [29], lycorine [30], curcumin [31], and other plant products have significant anti-tumor activities, including the inhibition of tumor cell growth and metastasis. In addition, most traditional Chinese medicines have significantly fewer adverse effects than chemotherapy, but with comparable therapeutic effects [32].…”
Section: Discussionmentioning
confidence: 99%